Predictable Irrationality in Mediation: Observations on Behavioural Economics - Antal, Orsolya (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
In my paper I attempt to provide a common intersection of mediation and behavioural economics. In doing so, I seek to identify the answers that can be used to assign the domain of mediation methodology where theorems of man's decisions of behavioural economics are validated. I seek to identify the answers that can be used to the domain of mediation methodology where behavioural economics can be applied to the theorems of man's choices. I do so in order to take account the phenomena behind human decisions, influencing them and determining their characteristics. Through this, I seek to prove the proposition that human behaviour is neither logical nor rational, a claim which plays an important role in mediation. Beyond this, the study discusses the statements of behavioural economics which also prove the above theorem. However, the aim of the paper is also to collide the results of behavioural economics with the practical experience of mediation, thereby answering the question whether theoretical results of behavioural economics on human decisions are validated in practice. The essence of mediation is to reach a favourable agreement, the in-process tool of which will influence human behaviour and decision-making towards this goal. In my study, accordingly, I intend to achieve the goal of naming the mediation techniques and tools that can be used to achieve the outcome of mediation that is a good agreement.